Multimedia Technology in English Language Teaching: Advantages or Disadvantages? - Keumala, Meta; Idami, Zahratul; Zakaria, Zakaria (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Multimedia technology integration has grown in popularity in the ever-changing field of modern education, providing a more comprehensive method of instruction. Three English instructors at an Islamic Senior High School in Aceh Besar provided the data for this study, which used a qualitative methodology, between January 22 and 27, 2024. The interview and observation guide sheet were constructed based on Pun (2013) about the advantages and disadvantages of the use of multimedia technology in English language teaching. Data analysis from observation and interviews was done qualitatively. The results show that Class 1 was taught by T1 whose focused on teaching grammar skill to 19 students of the first grade of senior high school. The results of the quiz showed that there were 3 students who got low scores (60,50,40), 7 students got 75-85 and 9 students were all correct (100). Class 2 shows that T2 taught speaking skills through a YouTube channel and 22 students were participating in the class. Class 3 shows that teacher teaches reading skills employed an online reading website named "Perussall”